Komunikasi Matematis Siswa Tunarungu dalam Pembelajaran Matematika didasarkan pada Teori Schoenfeld - Mujib, Mujib (Universitas Islam Raden Intan Lampung, INDONESIA, 2016)
This research was conducted at SMALB Dharma Wanita Pertiwi Bandar Lampung. The subjects of this study were 2 students of hearing impaired class XI. Data analysis techniques are performed by: (1) grouping data into 4 categories: (a) analyzing and understanding problems (b) designing and planning solutions (c) exploring solutions to difficult problems (d) verifying solutions, then reducing data that is not Including in the four categories, (2) present data in the form of narrative text, and (3) summarize the students' deaf mathematical communication. The results of this study indicate that (1) In the stage of analyzing and understanding the problem, students receive direct information received from the problem and convert it into the form of images. (2) At the stage of designing and planning solutions, students look at the problem information to solve the problem so that in their thinking is a global idea of the problem. (3) At the stage of exploring solutions to difficult problems, students work on problems using formulas and methods that are designed and planned in advance. (4) In the stage of verifying the solution, the student simply checks the formula that has been written and checks the answer.